Relações públicas de dados: possibilidades e responsabilidades da profissão na Era da informação - Raitz, Carolina Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The Information Age brings change in a speed parallel to the growing capacity of information processing, causing an irreversible shift in the way of working with communication. The present work has the goal to bring up reflections with respect to the role of the Public Relations professional in the context of the Information Age, and mostly spark a discussion in attempt to get a glimpse into how big data and artificial intelligence might influence this practice and how data, which takes up an increasingly bigger part in the center of organizational strategy, can be assimilated by this practice. Through bibliographic research, information was gathered regarding the relation between work and technology through history, to try to comprehend how technology has influenced changes in the occupational structure. After that a reflection was made in regard to technology and employment in the Information Age, in search of an understanding of how the unprecedented advances in artificial intelligence can threaten the workforce. Finally, we sought to develop further the specific case of Public Relations, as to its employability and its practices, as well as the ways to keep the profession relevant in the information economy. We proposed reflections about how Public Relations can work with data, which new responsibilities and possibilities arise in the ever-changing world. The results of this reflection show that, just like it once happened with social media and information and communication technologies, it’s a matter of time before the work with data, now optional and even differential, becomes a requirement for the public relations professional to keep their strategic seat on the organizations’ table.

A Era da Informação traz mudanças em uma curva paralela à crescente capacidade de processamento de informação com alterações irreversíveis na forma de trabalhar a comunicação. O presente trabalho tem como objetivo despertar reflexões sobre o papel do Relações Públicas no contexto da Era da Informação, sobretudo discutindo e tentando vislumbrar como a big data e a inteligência artificial podem influenciar esta profissão e como os dados, que assumem um papel cada vez mais central na estratégia organizacional, podem ser assimilados na prática desse profissional. A partir de pesquisa bibliográfica, realizou-se um levantamento sobre a relação entre trabalho e tecnologia através da história, para nesse contexto compreender de que forma a tecnologia influenciou as mudanças na configuração da estrutura ocupacional. Depois disso foi elaborada uma reflexão a respeito da tecnologia e do emprego na Era da Informação, na busca de compreender de que forma os avanços inéditos na inteligência artificial podem ameaçar a força de trabalho. Finalmente, procurou-se aprofundar no caso específico das Relações Públicas, sobre sua condição de emprego e suas práticas, bem como as formas de manter-se relevante na economia da informação. Foram propostas reflexões a respeito do trabalho de Relações Públicas com dados, quais as novas responsabilidades e possibilidades que surgem no mundo em transformação. Os resultados desta reflexão apontam que, assim como foi com as mídias sociais e as tecnologias de informação e comunicação, é uma questão de tempo para que o trabalho com dados, hoje opcional e até um diferencial, se torne um pré-requisito para que o profissional de relações públicas continue ocupando uma posição estratégica dentro das organizações.
Data Public Relations: possibilities and responsibilities of the profession in the information age
Keywords: Big data; Public relations; Data; Information age; Technology; Artificial intelligence; Relações Públicas; Dados; Era da Informação; Tecnologia; Inteligência artificial